2017
DOI: 10.1021/acs.jafc.6b04829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Male-Produced Aggregation Pheromone of the Four-Spotted Coconut Weevil, Diocalandra frumenti

Abstract: 20The four-spotted coconut weevil, Diocalandra frumenti Fabricius (Coleoptera: 21 Curculionidae), is a small weevil found attacking economically important palm species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Mated females were sampled on the lemons from the main stock colony after checking for the presence of ovisacs. The production of sex pheromone was confirmed by collection of emitted volatiles from a group of 20−30 virgin females by solid phase microextraction technique (SPME) (Vacas et al, 2017). The identity of the sex pheromone was unequivocally confirmed by full coincidence of its mass spectra and retention time with an analytical standard sample synthesised according to the method described by Kukovinets et al, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Mated females were sampled on the lemons from the main stock colony after checking for the presence of ovisacs. The production of sex pheromone was confirmed by collection of emitted volatiles from a group of 20−30 virgin females by solid phase microextraction technique (SPME) (Vacas et al, 2017). The identity of the sex pheromone was unequivocally confirmed by full coincidence of its mass spectra and retention time with an analytical standard sample synthesised according to the method described by Kukovinets et al, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…They also concluded that this pest was not only affect on the young fruits, but also on the mature fruits. Report by Vacas et al (2017) also stated that this species is difficult to recognize with popular symptoms such as emergence holes, fruit fall, gum exudate.…”
Section: Attack and Damage Behavior Of Diocalandra Frumentimentioning
confidence: 99%
“…The European and Mediterranean Plant Protection Organization (EPPO 2012) reported that tts damages can cause fruit deformity and stunting. Larvae attack the tissues of trunks and leaves and causing gum exudation, yellowing of leaves (Vacas et al 2017). According to Vacas et al (2017), D. frumenti has been identified as an important pest in economically valuable palm species, including Date palm and Canary palm.…”
Section: Introductionmentioning
confidence: 99%